A Comprehensive Study on Cognitive Radio Based Internet of Things - Afzal, H.; Aslam, W.; Mufti, M.R. (The Nucleus, 2019)
The extension of Internet to the physical world realizes the Internet of Things (IoT). It increasingly connects heterogeneous devices wirelessly for remotely accessing and controlling them. IoT devices mostly use unlicensed wireless spectrum bands. Soon these bands will become congested creating collisions among users and thus resulting in spectrum scarcity problem. In order to support massive deployment of IoT systems, the radio spectrum must be used efficiently. Cognitive Radio (CR) is an emergent technology that overcomes this problem by efficient utilization of spectrum, ensuring reliability. CR is based on opportunistic use of licensed radio spectrum whenever it is sensed free. Thus CR based IoT is a promising research area, though posing challenges that must be tackled before its acceptance as a technology. In this paper, first IoT and CR are elaborated individually and then CR based IoT systems are discussed.